Surgical and survival outcomes of neoadjuvant IMRT-based chemoradiotherapy versus upfront surgery in borderline resectable pancreatic cancer: a retrospective cohort study - Huang, Xinru; Yang, Hui; Cai, Wentao (Frontiers in Oncology, 2026)
BackgroundBorderline resectable pancreatic cancer (BRPC) poses significant surgical challenges due to tumor-vessel involvement and high risk of positive margins and early recurrence. While neoadjuvant chemoradiotherapy has demonstrated potential benefits in this setting, the role of intensity-modulated radiation therapy (IMRT) combined with gemcitabine and nab-paclitaxel has not been specifically evaluated.MethodsIn this single-center retrospective cohort study, we analyzed patients with histologically confirmed borderline resectable pancreatic ductal adenocarcinoma treated between 2019 and 2022 who ultimately underwent curative-intent resection. Patients either underwent upfront surgery or received neoadjuvant chemoradiotherapy consisting of gemcitabine (1000 mg/m²) and nab-paclitaxel (125 mg/m²) combined with IMRT (36 Gy in 20 fractions), followed by surgery when feasible. Overall survival (OS) and recurrence-free survival (RFS) were calculated from the date of surgery. To address baseline imbalances, propensity score overlap weighting was performed to estimate the average treatment effect in the overlap population (ATO).ResultsA total of 152 patients were included, with 109 in the upfront surgery group and 43 in the chemoradiotherapy group. In unweighted analyses, median RFS was 27 months (95% CI 20.4-33.6) in the chemoradiotherapy group versus 13 months (95% CI 8.2-17.8) in the upfront surgery group (HR 0.61, 95% CI 0.39-0.94; p=0.026), and median OS was 33 months (95% CI 19.5-46.5) versus 21 months (95% CI 14.1-28.0) (HR 0.58, 95% CI 0.36-0.94; p=0.027). In ATO-weighted analyses, median RFS was 25 months (95% CI 14-not reached) versus 11 months (95% CI 8-17) (HR 0.56, 95% CI 0.35-0.88; p=0.013), and median OS was 33 months (95% CI 19-not reached) versus 17 months (95% CI 14-24) (HR 0.56, 95% CI 0.34-0.94; p=0.027).ConclusionNeoadjuvant chemoradiotherapy with IMRT plus gemcitabine and nab-paclitaxel was associated with improved surgical and survival outcomes in patients with BRPC compared to upfront surgery. These findings support the integration of modern chemoradiotherapy into the neoadjuvant treatment paradigm for BRPC and warrant prospective validation.